Sosiologi Kesehatan Dalam Praktik: Pelatihan Dan Penyuluhan Perubahan Gaya Hidup Untuk Mengurangi Risiko Asam Urat Pada Komunitas Lansia Desa B Tahun 2025 - Meiana Harfika; Jukarnain Jukarnain; Nurhaedah Nurhaedah; Nursinah Nursinah (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2025)
Gout or gouty arthritis cases are increasing among the elderly due to unhealthy lifestyles, such as high-purine food consumption, lack of physical activity, and minimal awareness of the importance of healthy behaviors. This community service activity aims to improve the knowledge and behavior of the elderly in preventing gout through a sociology of health approach, which emphasizes behavioral change based on social interactions, cultural values, and community norms. The implementation method included counseling, training in healthy lifestyle practices, group discussions, and pre- and post-test evaluations. The activity was conducted in Village B, South Sulawesi, involving 30 elderly participants. The materials provided included education on low-purine nutrition, light physical exercise, and the formation of a social support group "Healthy Elderly Without Gout." The activity results showed a significant increase in participants' knowledge of 70% after the training and an increase in healthy behaviors, such as reducing offal consumption and increasing physical activity. The sociology of health approach has proven effective because it prioritizes behavioral change based on social support and community learning, rather than solely individual medical interventions. Conclusion: This activity successfully promoted healthy lifestyle changes in the elderly through an integrated social and educational approach. Sustainable programs with cross-sector collaboration are needed to ensure long-term sustainability of behavioral changes.